2005
DOI: 10.1016/j.biocontrol.2004.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of bacterial spot of tomato under field conditions at several locations in North America

Abstract: Biological Control 32 (2005) 408-418. doi:10.1016/j.biocontrol.2004.12.001Received by publisher: 2004-09-01Harvest Date: 2016-01-04 12:23:12DOI: 10.1016/j.biocontrol.2004.12.001Page Range: 408-41

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 36 publications
3
25
1
1
Order By: Relevance
“…The percentages of disease control obtained in the present study were higher than those found by Byrne et al (2005) and Kavitha & Umesha (2007) for the same pathosystem. These authors reported 36.4% disease control using Pseudomonas syringae and 20 to 30% using P. fluorescens, respectively.…”
contrasting
confidence: 85%
See 1 more Smart Citation
“…The percentages of disease control obtained in the present study were higher than those found by Byrne et al (2005) and Kavitha & Umesha (2007) for the same pathosystem. These authors reported 36.4% disease control using Pseudomonas syringae and 20 to 30% using P. fluorescens, respectively.…”
contrasting
confidence: 85%
“…The variability in the efficacy of control of bacterial spot for the isolates used in this work (except for DFs1420) was previously registeded by Ludwig & Moura (2007) and it was associated with the stage of plant development, geographical areas (Byrne et al, 2005) or cultivars (Kavitha & Umesha, 2007). The stability of the control by the microorganism is usually associated with the performance of multiple mechanisms of action (Guetsky et al, 2001) and with an aggressive colonization of the tissues of the host plant (Kloepper & Beauchamp, 1992).…”
Section: Biological Control Of Tomato Bacterial Spot By Seed Microbiomentioning
confidence: 93%
“…Many authors reported the use of antagonistic microorganisms such as fungi, rhizobacteria and especially bacteria of genus Bacillus and Pseudomonas as biocontrol agents for plant diseases (Shoda, 2000;Byrne et al, 2005;Lemessa & Zeller, 2007;Todorova & Kozhuharova, 2010). However, there are few reports about the use of microorganisms or secondary metabolic compounds in the control of X. axonopodis of eucalyptus.…”
Section: Discussionmentioning
confidence: 99%
“…Use of biocontrol agents is a viable alternative to pesticides, and a promising strategy in managing plant diseases (Shoda, 2000;Byrne et al, 2005;Ran et al, 2005;Lemessa & Zeller, 2007). The antibiotic compounds produced by antagonistic species, when in competition, can inhibit the growth of pathogenic species.…”
Section: Introductionmentioning
confidence: 99%
“…Os mecanismos de promoção de crescimento pelas bactérias epifíticas e endofíticas incluem diferentes ações, como a fixação biológica de nitrogênio (KuKlinsky-Sobral et al, 2004), solubilização de fosfatos (Chabot et al, 1998;Verma et al, 2001), biossíntese de fito-hormônios (Lucangeli & Bottini, 1997), influência na atividade enzimática da 1-aminociclopropano 1-carboxilato (ACC) deaminase (Rothballer at al., 2008), controle biológico (Byrne et al, 2005), síntese de sideróforos (Lacava et al, 2008) e indução de resistência sistêmica a patógenos na planta hospedeira (Kloepper et al, 1999 Efeitos positivos da inoculação de bactérias promotoras de crescimento foram verificados na abacaxicultura, principalmente quando as bactérias inoculadas também são fixadoras de nitrogênio atmosférico (Weber et al, 2003). Já foram isoladas de abacaxizeiros bactérias diazotróficas pertencentes aos gêneros Burkholderia (Weber et al, 1999), Acetobacter (Tapia-Hernández et al, 2000) e Asaia (Weber et al, 2003).…”
Section: Introductionunclassified